2004
DOI: 10.1007/s10038-004-0145-4
|View full text |Cite
|
Sign up to set email alerts
|

The de novo chromosome 16 translocations of two patients with abnormal phenotypes (mental retardation and epilepsy) disrupt the A2BP1 gene

Abstract: The 16p13.3 breakpoints of two de novo translocations of chromosome 16, t(1;16) and t(14;16), were shown by initial mapping studies to have physically adjacent breakpoints. The translocations were ascertained in patients with abnormal phenotypes characterized by predominant epilepsy in one patient and mental retardation in the other. Distamycin/DAPI banding showed that the chromosome 1 breakpoint of the t(1;16) was in the pericentric heterochromatin therefore restricting potential gene disruption to the 16p13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(139 citation statements)
references
References 4 publications
7
130
0
2
Order By: Relevance
“…RBFOX proteins have a single RRM, highly homologous among the three paralogs, and their binding sites are exceptionally highly conserved in sequence (UGCAUG) and position across vertebrate evolution (Sun et al 2012). Mutations or deletions in RBFOX1 and RBFOX3 are found in epilepsy patients (Bhalla et al 2004;Lal et al 2013a,b), whereas copy-number variations in RBFOX1 are associated with autism spectrum disorders and spinocerebellar ataxias (Bill et al 2013;Weyn-Vanhentenryck et al 2014). Mouse models with Rbfox KO or KD show extensive defects in neuronal and muscle physiology, suggesting that these proteins play key roles in normal development (Gehman et al 2011(Gehman et al , 2012.…”
Section: Rbfox2-rna Binding Protein Fox-2 Homologmentioning
confidence: 99%
“…RBFOX proteins have a single RRM, highly homologous among the three paralogs, and their binding sites are exceptionally highly conserved in sequence (UGCAUG) and position across vertebrate evolution (Sun et al 2012). Mutations or deletions in RBFOX1 and RBFOX3 are found in epilepsy patients (Bhalla et al 2004;Lal et al 2013a,b), whereas copy-number variations in RBFOX1 are associated with autism spectrum disorders and spinocerebellar ataxias (Bill et al 2013;Weyn-Vanhentenryck et al 2014). Mouse models with Rbfox KO or KD show extensive defects in neuronal and muscle physiology, suggesting that these proteins play key roles in normal development (Gehman et al 2011(Gehman et al , 2012.…”
Section: Rbfox2-rna Binding Protein Fox-2 Homologmentioning
confidence: 99%
“…Studies in knock-out mice and in human neural stem cells showed that Rbfox1 regulates neuronal development and excitability (32, 51), whereas Rbfox2 affects neuron migration in the cerebellum (52). In addition, mutations in Rbfox1 are found in patients with epilepsy, spinocerebellar ataxia, and autism spectrum disorders (53)(54)(55)(56). In skeletal muscle, the absence of Rbfox1 leads to abnormal myofibrillar structure and impaired muscle function (57).…”
Section: Role Of Neuron-enriched Rna-binding Proteins In Beta Cellsmentioning
confidence: 99%
“…Additionally, genes with Fox-dependent AS events were frequently associated with diseases, including several neurological, heart, and muscular disorders. Mutations in the Fox-1 gene or alteration of its expression has been associated with several neurological disorders and heart disease (Kaynak et al 2003;Bhalla et al 2004;Szatmari et al 2007), thus making the identified splicing regulatory network an excellent data set to identify potentially interesting relationships between RNA targets and the etiology of some of these diseases.…”
Section: Fox Splicing Regulatorsmentioning
confidence: 99%